Diversity of Insects in Cocoa (Theobroma cacao L.) Plantations with Integrated Pest Management (IPM) and Non IPM in Biru-biru District of Deli Serdang Regency - Jemahaganta Surbakti; Suzanna Fitriany Sitepu; Syahrial Oemry (Jurnal Agroekoteknologi, 2018)
The cocoa farmers mostly practice conventional pest control that can be harmful to the environment, therefore integrated pest management has been developed. This research aimed to know diversity of insects in cocoa plantations affected by integrated pest management (IPM) and conventional (non IPM) techniques. This research was conducted in two villages in Biru-Biru District, Deli Serdang Regency and in Plant Pests Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, Medan from June until September 2016. This research used four insect traps (sweep net, pitfall trap, light trap, and yellow trap), and repeated five times. The results showed that insects caught on cocoa plantations with IPM were 12 orders and 44 families, the highest relative density value was 27.49%, the lowest was 0.07%, the index value of insect diversity Shannon-Weiner (H') was 2.90 (moderate) and the index value of insect evenness (E) was 0.76 (high) whereas on cocoa plantations with non IPM were 10 Orders and 39 families with the highest relative density value was 25.27%, the lowest was 0.10%, the index value of insect diversity Shannon-Weiner (H') was 2.76 (moderate) and the index value of insect evenness (E) was 0.75 (high). Keywords:  biodiversity, cocoa, insects, integrated pest management